If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -91 = p + -6(-1p + 7) Reorder the terms: -91 = p + -6(7 + -1p) -91 = p + (7 * -6 + -1p * -6) -91 = p + (-42 + 6p) Reorder the terms: -91 = -42 + p + 6p Combine like terms: p + 6p = 7p -91 = -42 + 7p Solving -91 = -42 + 7p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7p' to each side of the equation. -91 + -7p = -42 + 7p + -7p Combine like terms: 7p + -7p = 0 -91 + -7p = -42 + 0 -91 + -7p = -42 Add '91' to each side of the equation. -91 + 91 + -7p = -42 + 91 Combine like terms: -91 + 91 = 0 0 + -7p = -42 + 91 -7p = -42 + 91 Combine like terms: -42 + 91 = 49 -7p = 49 Divide each side by '-7'. p = -7 Simplifying p = -7
| -17x-23x=12x-2 | | -17x-23x=12x-2 | | x^2-x-6%x^2-5x+6 | | f(x)=zx^2+12x+14 | | 2(u-8)-1=-5(-5u+4)-5u | | (-15)+e=12 | | 12x=121 | | 45-2x(15-2)= | | 3v-12=2 | | 3x^20=41 | | 8(3m+1)= | | 5(-x+10)=5x+10 | | x+37=7 | | 19=-3.1+j | | 3(12)=y | | -8n+4(1+5a)=-6n-14 | | x-z=15 | | 6z+1=.30 | | -6(6n+5)=38-2n | | 3u-9+2(2u+3)=-7(u+3) | | x^2+25x-444=0 | | 1.3z-0.7(z+13)=0.6(z+5) | | -6(6n+5)=38-2n | | x^2+25x-444=0 | | 2e^6x=5e^9x | | .3333333333333y=6 | | 1.3z-0.7(z+13)=0.6(z+5) | | 2e^6x=5e^9x | | 1.3z-0.7(z+13)=0.6(z+5) | | 0+.3333333333333333y=6 | | 0+.3333333333333333y=6 | | 1.3z-0.7(z+13)=0.6(z+5) |